2014
DOI: 10.1115/1.4026409
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Finite Element Analysis of Human Vertebral Collapse Under Large Compressive Strains

Abstract: Osteoporosis-related vertebral fractures represent a major health problem in elderly populations. Such fractures can often only be diagnosed after a substantial deformation history of the vertebral body. Therefore, it remains a challenge for clinicians to distinguish between stable and progressive potentially harmful fractures. Accordingly, novel criteria for selection of the appropriate conservative or surgical treatment are urgently needed. Computer tomography-based finite element analysis is an increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Large errors in FE predictions were found for both sets of material properties, which differed in elastic anisotropy and yield criterion but not post-yield constitutive behavior. Recent studies have shown good qualitative correspondence between patterns of frank vertebral collapse observed at very large applied displacements vs. patterns predicted by FE analyses using a damage-plastic constitutive model (Clouthier et al, 2015; Hosseini et al, 2014). In contrast, further refinements to the modeling of elastic anisotropy have only a minor effect on FE predictions of vertebral deformation (Unnikrishnan et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Large errors in FE predictions were found for both sets of material properties, which differed in elastic anisotropy and yield criterion but not post-yield constitutive behavior. Recent studies have shown good qualitative correspondence between patterns of frank vertebral collapse observed at very large applied displacements vs. patterns predicted by FE analyses using a damage-plastic constitutive model (Clouthier et al, 2015; Hosseini et al, 2014). In contrast, further refinements to the modeling of elastic anisotropy have only a minor effect on FE predictions of vertebral deformation (Unnikrishnan et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…This finding may be particularly important for future fracture risk, as damage within vertebral bodies has been shown to initiate within the trabecular bone compartment [34,35]. For example, Eswaran et al showed that during compressive loading of human vertebral bodies, high-risk tissue was first observed in the trabecular bone region, and the largest proportion of high-risk bone tissue was in the trabecular bone [34].…”
Section: Discussionmentioning
confidence: 99%
“…The nonlocal damage variable ensures preventing the localization of the inelastic process into an arbitrarily small volume. The Helmholtz Equation (33) is solved together with the balance of linear momentum Equation (35) to take into account the effect of damage induced by the plastic strain at the neighboring integration points. This results in reduced mesh dependency of the classical local model beyond the peak.…”
Section: Over-nonlocal Damage-plastic Model For Trabecular Bonementioning
confidence: 99%
“…is the non-standard internal force vector, related to the discrete form of Helmholtz equation (33). Satisfaction of the governing equations in the weak sense is tested for the state at the end of the step.…”
Section: Spatial Discretization Of the Principle Of Virtual Powermentioning
confidence: 99%